Kill and Chill: Restructuring Canada's Beef Commodity Chain - Loch-Drake, Cynthia (Labour / Le Travail, 2004)
The article reviews the book, "Kill and Chill: Restructuring Canada's Beef Commodity Chain," by Ian MacLachlan.